KINEMATIC AND DYNAMIC WAVE APPLICATION ON RAINFALL-RUNOFF MODEL (CASE STUDY UPPER CITARUM WATERSHED) - LOKANTARA (NIM 25005027), HARSIGIT
A distributed conceptual rainfall-runoff model applied to 13 catchments in the Upper Citarum Watershed for the purpose of kinematic and dynamic wave effect modeling on the runoff distribution. An approach to calibrate the model by associating the model parameters with the physical catchments characteristics was implemented. Land uses, catchments grid size, and topographic structures were used as the bases for regionalization of the model parameters. Parameter values were initially associated with these catchments characteristics and were finally transferred into their catchments grid scale values. Kinematic wave propagation was performed to distribute runoff as overland flow and channel flow along the tributaries. As the result, an outlet hydrograph obtained for each tributary. Thirteen tributary outlet hydrographs continually distributed along the main river (Citarum River) by dynamic wave propagation using Abbott-Ioneschu scheme and yield the final hydrograph at Nanjung outlet. Nanjung outlet hydrograph obtained from model finally verified with the Nanjung observe discharge. As the result, kinematic wave propagation was not satisfying for distributing runoff at a particular point in the land or channel with a mild slope. This method has no hydraulic mechanisms to describe upstream propagation as kinematic wave neglecting the dynamic terms.